Early-Onset Fulminant Sepsis in a Preterm Neonate due to Streptococcus gallolyticus: A Case Report and Literature Review - Williams, Chandler; Sakaria, Rishika P.; Pourcyrous, Massroor (American Journal of Perinatology Reports, 2022)
Streptococcus gallolyticus is an uncommon cause of neonatal infections. We describe the first case of fulminant lethal neonatal sepsis due to S. gallolyticus reported in literature. Our patient was an extremely low birth weight premature infant born to a mother with prolonged rupture of amniotic membranes and chorioamnionitis. We also review the cases of neonatal S. gallolyticus infections reported in literature. Fifty-eight percent neonatal S. gallolyticus infections presented in the first week of life. Importantly, S. gallolyticus meningitis is more commonly reported with early-onset infections compared with group B streptococcal meningitis, which is more common with late-onset infections. Streptococcus gallolyticus should be included in differential for neonatal sepsis, particularly in the presence of meningitis in the first week of life. Most cases are sensitive to penicillin; however, cases of reduced sensitivity to penicillin have also been reported.
Keywords: neonatal sepsis; Streptococcus bovis; Streptococcus gallolyticus; Streptococcus pasteurianus; neonatal meningitis; chorioamnionitis; preterm